Dismantling Institutional Whiteness Emerging Forms of Leadership in Higher Education - Alcalde, M. Cristina; Subramaniam, Mangala (Purdue University Press, 2022)
Dismantling Institutional Whiteness: Emerging Forms of Leadership in Higher Education focuses on the experiences of women of color in leadership roles in higher education. Top roles historically have gone to white men, and leadership has not reflected the range of identities and people who make up higher education. Why? And why does this problem continue to this day? Most importantly, what can be done to bring about meaningful change?Dismantling Institutional Whiteness gathers a range of first-person narratives from women of color and examines the challenges they face not only at a systemic level, but also at a deeply personal level. Their experiences combined with research and statistics paint a sobering portrait of higher education's problems when it comes to diversity, equity, and inclusion. Interspersed throughout their stories are practical suggestions for how to address inequity in higher education, and to give a voice to people who have been silenced and excluded. Whether a trustee, university executive, or faculty member at any level, this is essential reading for those interested in diversifying higher education leadership to ensure decisions reflect the priorities of all.